The “Great Return” to Liberated Territories: Exploring the Prospects and Challenges of Urban-rural Migration - Aliyeva, Fidan; Eyvazli, Kanan; Bayalizada, Nuhbaba (ADA University, 2023)
The liberation of Karabakh after 30 years has created opportunities to relocate the Azerbaijani IDPs back to their hometowns. Therefore, the government of Azerbaijan has established the “Great Return’’ program in terms of restoring infrastructure and improving the living conditions of the Azerbaijani IDPs in the liberated territories. Thus, this capstone project aims to analyze the possible strategy challenges of urban-rural migration in the “Great Return” program. To identify the willingness of the Azerbaijani IDPs to resettle in their hometowns, seven semi-structured interviewees from different regions of the liberated areas were selected. Interview results show that IDPs have access to various employment options and advanced healthcare services in Baku. Therefore, they are reluctant to move to the liberated areas. This study focuses on the policy alternative of developing regions by decentralizing Baku to reduce overpopulation and create residential, educational, and professional opportunities in the newly liberated territories of Karabakh. The research recommends that providing education and employment opportunities to IDPs can make the region more appealing for their relocation. Additionally, it suggests that clearing landmines and maintaining the peace treaty can stabilize the economy in the liberated areas and improve relations with neighboring regions.
Keywords: Internally displaced persons -- Azerbaijan; Urban-rural migration -- Azerbaijan; Regional development -- Azerbaijan; Public and International Affairs